Achieving access to haemophilia care in low-income and lower-middle-income countries: expanded Humanitarian Aid Program of the World Federation of Hemophilia after 5 years. Issue 9 (September 2022) - Pierce, Glenn F; Adediran, Megan; Diop, Saliou; Dunn, Amy L; El Ekiaby, Magdy; Kaczmarek, Radoslaw; Konkle, Barbara A; Pipe, Steven W; Skinner, Mark W; Valentino, Leonard A; Robinson, Fiona; Ampartzidis, Georgios; et al.
Summary: Highly effective treatment of haemophilia A and B is primarily available to 15% of the world's population, in high-income countries. In low-income countries (LICs) and lower-middle-income countries (LMICs), morbidity and mortality are high because of greatly reduced access to diagnosis, care, and treatment. We report the challenges and impact after the first 5 years (mid-2015–2020) of the expanded World Federation of Hemophilia (WFH) Humanitarian Aid Program (HAP). WFH HAP donated coagulation products were used to treat more than 250 000 acute bleeding episodes, manage approximately 4000 surgeries, and establish bleeding preventive prophylaxis in about 2000 patients in 73 countries. Health-care providers worldwide learned optimal management of patients with complex needs through virtual and in-person training. In response to the programme, some governments increased investment in haemophilia care, including independent purchases of small amounts of treatment products. With unparalleled scope and complexity, and substantial benefits to people with haemophilia and society in general, the WFH HAP is an exemplar of partnership between for-profit and not-for-profit organisations advancing health-care equity in LICs and LMICs, which could be replicated by other organisations supporting people with different monogenic diseases.